2016
DOI: 10.3390/safety2020010
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Side-by-Side Vehicle Crashes and Related Injuries as Determined Using Newspaper Reports from Nine U.S. States

Abstract: Abstract:Side-by-side (SxS) vehicles have become increasingly popular, but there are few reports on injury epidemiology. Newspaper reports of SxS and all-terrain vehicle (ATV) crashes were analyzed for nine U.S. states from 2009 to 2011, including comparisons between the two vehicle types. Seventy-nine SxS crashes involving 104 injured victims were identified; three-fourths were males. There was a relatively high percentage of injured passengers (37%), and a higher proportion of female victims were passengers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(33 citation statements)
references
References 18 publications
8
25
0
Order By: Relevance
“…Almost two-thirds of patients in our study were males. This proportion is similar to the 2016 CPSC report (68%), the 2018 CPSC/FARS study (71%), and the newspaper article study (70%) (U.S. Consumer Product Safety Commission, 2016; Richardson et al, 2018;Jennissen et al, 2016). In contrast, the pediatric trauma center study reported males comprised only 55% of victims (Linnaus et al, 2017).…”
Section: Demographicssupporting
confidence: 72%
See 2 more Smart Citations
“…Almost two-thirds of patients in our study were males. This proportion is similar to the 2016 CPSC report (68%), the 2018 CPSC/FARS study (71%), and the newspaper article study (70%) (U.S. Consumer Product Safety Commission, 2016; Richardson et al, 2018;Jennissen et al, 2016). In contrast, the pediatric trauma center study reported males comprised only 55% of victims (Linnaus et al, 2017).…”
Section: Demographicssupporting
confidence: 72%
“…Consistent with this, we found about half of those injured were passengers. The newspaper article study reported passengers were 37% of victims (Jennissen et al, 2016). In contrast to ROVs, almost all ATVs are designed for an operator only, and previous studies found passengers were about 15-22% of ATV-related injuries and deaths (Jennissen et al, 2016;Denning et al, 2013a;Denning et al, 2013b;Denning et al, 2014;.…”
Section: Demographicsmentioning
confidence: 99%
See 1 more Smart Citation
“…ORVs are motorized vehicles with 3 or more wheels designed for use over off-road terrain, including all-terrain vehicles (ATVs) and side by sides (SxSs), which include both utility terrain vehicles and recreational off-highway vehicles. 1,2 ATVs are typically 4-wheeled ORVs with handlebars for steering and seats intended to be straddled by the driver. They have high centers of gravity and can achieve high speeds, making them unstable and unsafe for children.…”
mentioning
confidence: 99%
“…5,6 SxSs were involved in 335 fatalities and 506 injuries over a similar time frame, with drivers younger than 16 years old contributing to >50% of the incidents. 1,2 The significant morbidity and mortality associated with the use of ORVs by children has led to medical societies, legislators, and health care providers advocating for federal safety standards and injury prevention legislation. 3,5,7,8 ORV injury prevention efforts began in the late 1980s when the Consumer Product Safety Commission (CPSC) and members of the ATV industry entered a 10-year consent decree that included the banning of 3-wheeled vehicles, a free nationwide training program offered to purchasers of new ATVs, and age recommendations for ATV use.…”
mentioning
confidence: 99%